2010
DOI: 10.1002/chem.200901601
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Catalytic Activity for Oxidation Taking Place on Various TiO2 Surfaces with Surface OH Groups and Surface Oxygen Vacancies

Abstract: Three catalytic oxidation reactions have been studied: The ultraviolet (UV) light induced photocatalytic decomposition of the synthetic dye sulforhodamine B (SRB) in the presence of TiO(2) nanostructures in water, together with two reactions employing Au/TiO(2) nanostructure catalysts, namely, CO oxidation in air and the decomposition of formaldehyde under visible light irradiation. Four kinds of TiO(2) nanotubes and nanorods with different phases and compositions were prepared for this study, and gold nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…It can also be observed that at calcination temperatures of 500 and 550°C, the surface OH density of the RuO 2 /TiO 2 (SSSG) was somewhat higher than that of the RuO 2 /TiO 2 (IWI). This evidence is in agreement with a recent study [30], which reported that anatase TiO 2 not only has high surface OH density but also has high ability to generate OH group compared to other types of TiO 2 phases.…”
Section: Surface Oh Densitysupporting
confidence: 93%
“…It can also be observed that at calcination temperatures of 500 and 550°C, the surface OH density of the RuO 2 /TiO 2 (SSSG) was somewhat higher than that of the RuO 2 /TiO 2 (IWI). This evidence is in agreement with a recent study [30], which reported that anatase TiO 2 not only has high surface OH density but also has high ability to generate OH group compared to other types of TiO 2 phases.…”
Section: Surface Oh Densitysupporting
confidence: 93%
“…6a and b. The fringes with a spacing of 0.23 nm could be assigned to the (1 1 1) plane of the face-centered cubic gold crystal [44,52,53]. on the low-coordinated sites (e.g., corners, edges, etc.)…”
Section: Tem/hrtem Characterizationsmentioning
confidence: 99%
“…The peaks correspond respectively to the perovskite lattice oxygen at 529.89 eV (pink line), the oxygen vacancies at 530.76 eV (blue line) and the surface absorbed oxygen at 532.16 eV (green line) [33][34][35][36], indicating complicated states of oxygen in the film. The abundant surface absorbed oxygen would possibly act as an absorption source to absorb water, oxygen and even other small molecules from its surroundings [37], supplementing oxygen vacancies to the film. Therefore, the XPS result evidences the existence of large amounts of oxygen vacancies on the film surface, which can provide large quantity of trapping sites for electrons and contribute to the formation of conductive filament.…”
Section: Resultsmentioning
confidence: 99%